2010
DOI: 10.1227/01.neu.0000371979.48809.d9
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lung Injury Is an Independent Risk Factor for Brain Hypoxia After Severe Traumatic Brain Injury

Abstract: After severe TBI, PbtO2 correlates with PF ratio. Acute lung injury is associated with an increased risk of compromised PbtO2, independent from intracerebral and systemic injuries. Our findings support the use of lung-protective strategies to prevent brain hypoxia in TBI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…Its severity is related to the magnitude of the brain injury and it is associated with high morbidity rates and up to 7% mortality. 8,10,25 NPE may be triggered by different brain conditions, including seizures, stroke and traumatic brain injury ( Figure 3). NPE is most common in seizures during the post-critical period, affecting to up to one third of patients in status epilepticus.…”
Section: Neurogenic Pulmonary Edema (Npe)mentioning
confidence: 99%
“…Its severity is related to the magnitude of the brain injury and it is associated with high morbidity rates and up to 7% mortality. 8,10,25 NPE may be triggered by different brain conditions, including seizures, stroke and traumatic brain injury ( Figure 3). NPE is most common in seizures during the post-critical period, affecting to up to one third of patients in status epilepticus.…”
Section: Neurogenic Pulmonary Edema (Npe)mentioning
confidence: 99%
“…Based on the formula PbtO 2 = CBF ∙ AVTO 2 , reduced PbtO 2 occurs frequently because of low CBF. However, PaO 2 also is an important determinant of PbtO 2 [42] and additional pathological events (e.g., impaired lung function [43] or impaired O 2 extraction due to increased gradients for oxygen diffusion in injured brain tissue [17]) might reduce PbtO 2 , in the absence of reduced CBF. Hemoglobin concentration also affects PbtO 2 and reduced hemoglobin concentration below 9 g/dl may aggravate brain hypoxia [44].…”
Section: Bedside Clinical Approachmentioning
confidence: 99%
“…High altitude is a low-pressure and hypoxic environment and it has been demonstrated that acute hypoxia can cause injury to a number of organs (13). The specialized blood supply and anatomical structure of the intestine increases its sensitivity to hypoxia, which makes the intestine vulnerable to the effects of hypoxic stress (46).…”
Section: Introductionmentioning
confidence: 99%